Structural change in feedlot cattle death loss - Buda, Mark; Raper, Kellie C.; Riley, John Michael; Peel, Derrell; Lalman, David (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
When anecdotal evidence suggests that death loss in feedlots is increasing over time, it creates concern among producers because death loss affects pounds of saleable product and cost of gain. Death loss change could be driven by factors such as weather, technology adoption, feed rations, and cattle sourcing. If death loss is changing over time, it is important to understand the nature of the change. The changes can be constant over time or abrupt. Some events may or may not impact death loss. Some may have an immediate or delayed impact. Data from the Kansas Feedlot Performance and Feed Cost Summary, which consist of monthly summary of feedlot performance measures from January 1992 to July 2017, is used to model the death loss percentage over time. Structural change in this model is examined using cumulative sum (CUSUM) test, CUSUM of squares test, and tests by Bai and Perron. These tests can determine whether there are changes in death loss rates or not and identify the coinciding events.